Long-term results of teduglutide treatment for chronic intestinal failure – Insights from a national, multi-centric patient home-care service program. (October 2022) - Greif, Sophie; Maasberg, Sebastian; Wehkamp, Jan; Fusco, Stefano; Zopf, Yurdagül; Herrmann, Hans Joachim; Lamprecht, Georg; Jacob, Torid; Schiefke, Ingolf; von Websky, Martin W.; Büttner, Janine; Blüthner, Elisabeth; et al.
Summary: Background & aims: Teduglutide is a Glucagon-like peptide-2 (GLP-2) agonist indicated for the treatment of patients with parenteral support (PS) dependent short bowel syndrome (SBS) with chronic intestinal failure (cIF). Its application is accompanied by a structured nation-wide home-care service program in Germany. We investigated care characteristics and outcome parameters in a clinical real-world observational setting. Methods: Data generated within a therapy-accompanying home-care service program for adult SBS-cIF patients were analyzed retrospectively for patients treated up to 1 year (data cut: April 2020). Results: In total, 52 teduglutide-treated patients were included by 6 German cIF centers. At teduglutide administration start, 49/52 patients were on PS, 3 of them without macronutrients. The majority of patients received individualized parenteral nutrition (PN) (n = 32/46), while 13/46 were on commercial premixed bags. PS application was done by patients themselves (37%), home-care nurses (19%), relatives (8%) or by a combination of those (16%). In patients with PS dependency at baseline and available follow-up data (n = 40–44), teduglutide treatment resulted in significantly reduced PN days, caloric needs, infusion time, and infusion volume after 6 and 12 months. After 1 year, reduction of infusion time was positively correlated with a reduction of PN calories and volume; 30 patients (68%) were responders (PS-volume reduction ≥20%), and 6 patients (14%) were completely weaned off PS. Sleep disturbances per night were significantly reduced after 3 months of treatment and stool characteristics improved in consistency and significantly in frequency, while meal frequency remained stable. Conclusions: Teduglutide treatment associated reduction in PS volume and calories was accompanied by reduced infusion days, infusion times, sleep disturbances, stable oral intake surrogates, and improved stool characteristics, all of these potential parameters for improving quality of life. Furthermore, analyzed care characteristics reflect SBS-cIF treatment as a complex, resource-intensive and demanding task for both, healthcare system and patients.